Point of zero salt effect and its relationship with mineralogical and chemical properties of Brazilian oxisols - Silva, Marx Leandro Naves; Curi, Nilton; Marques, João José Granate de Sá e Melo; Guilherme, Luiz Roberto Guimães; de Lima, José Maria (Pesquisa Agropecuaria Brasileira, 1996)
The point of zero salt effect (PZSE) is an important parameter to study the surface charge of soil colloids, since, in relation to the actual pH, it allows to determine the net surface charge of soil particles. This paper aimed to determine the PZSE of oxisols of the experimental areas from the various Brazilian geographic regions and to correlate this parameter with electrochemical properties and mineralogical and chemical characteristics of these soils, as well as with the electrical potential of soil particles obtained by the Gouy-Chapman and Stem models. The PZSE was higher in those oxisols with higher gibbsite contents, and lower in those oxisols with higher contents of kaolinite, "total" Si and oxalate-Fe oxides, and with higher Ki and Kr. The mineralogical and chemical ratios presented higher correlations with PZSE than the absolute amounts, specially the Ki. The electric potential of the studied soils fits better to the Gouy-Chapman model than to the Stern one.
Keywords: PZSE; surface charge; electric potential